Orthogonal assays for the identification of inhibitors of the single-stranded nucleic acid binding protein YB-1 - AlexanderJ. Trevarton; Yan Zhou; Dehua Yang; Gordon W. Rewcastle; Jack U. Flanagan; Antony Braithwaite; Peter R. Shepherd; Cristin G. Print; Ming-Wei Wang; Annette Lasham (Elsevier, 2019)
We have previously shown that high expression of the nucleic acid binding factor YB-1 is strongly associated with poor prognosis in a variety of cancer types. The 3-dimensional protein structure of YB-1 has yet to be determined and its role in transcriptional regulation remains elusive. Drug targeting of transcription factors is often thought to be difficult and there are very few published high-throughput screening approaches. YB-1 predominantly binds to single-stranded nucleic acids, adding further difficulty to drug discovery. Therefore, we have developed two novel screening assays to detect compounds that interfere with the transcriptional activation properties of YB-1, both of which may be generalizable to screen for inhibitors of other nucleic acid binding molecules. The first approach is a cell-based luciferase reporter gene assay that measures the level of activation of a fragment of the E2F1 promoter by YB-1. The second approach is a novel application of the AlphaScreen system, to detect interference of YB-1 interaction with a single-stranded DNA binding site. These complementary assays examine YB-1 binding to two discrete nucleic acid sequences using two different luminescent signal outputs and were employed sequentially to screen 7360 small molecule compounds leading to the identification of three putative YB-1 inhibitors. Key words: Cancer, YB-1, Luciferase, AlphaScreen, Transcription factor, Single-stranded DNA